Basic college mathematics : - Bello, Ignacio (Prentice-Hall, 2009)
Basic College Mathematics will be a review of fundamental math concepts for some students and may break new ground for others. Nevertheless, students of all backgrounds will be delighted to find a refreshing book that appeals to all learning styles and reaches out to diverse demographics. Through down-to-earth explanations, patient skill-building, and exceptionally interesting and realistic applications, this worktext will empower students to learn and master mathematics in the real world.